Hiatal Hernia Presenting with Dyspnea - Konuk, Suat; Tug, Tuncer; Ballar, Manolya; Kayabasi, Ceyda (Archives of Clinical and Medical Case Reports, 2019)
Hiatal hernia is defined as the escape of abdominal organs to the thorax due to the anatomical weakness of the esophageal crus of the diaphragm. Hiatal hernia is often asymptomatic and causes gastroesophageal reflux when it is symptomatic. Patients with large hiatal hernias may have significant dyspnea and exercise disorder. The cause of dyspnea can be attributed mainly to large hernias in the thoracic cavity that cause left atrial compression, increase pulmonary venous pressure, produce interstitial edema and reduce pulmonary compliance. Here we present a 79-year-old female patient with hiatal hernia whose primary symptom is dyspnea. In the differential diagnosis of persistent dyspnea without a known cause, large hiatal hernias should be considered as a rare intraabdominal reason.